2002
DOI: 10.1097/01.prs.0000025183.78057.9b
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hand Compartment Syndromes after Closed Crush: A Reappraisal

Abstract: Severe crush to the hand is associated with a poor prognosis. The authors investigated the hypothesis that compartment syndrome complicates such injuries. From 1996 to 2000, the authors retrospectively identified 11 patients who, after sustaining a closed crush injury, developed acute hand compartment syndrome. Diagnosis was made on clinical grounds in two patients (the intracompartmental pressure was not measured) and after clinical examination plus measurement of intracompartmental pressure in nine patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…The clinical diagnosis of compartment syndrome was based on the presence of increasing pain with passive stretch of the fingers and the presence of massive swelling/tenderness on palpation. Similar to the findings of del Piñal et al (2002), we also found that hard swelling was the most important clinical sign. We also normally perform compartment pressure measurements, but these were not done in the current study because they were not available in that particular hospital.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…The clinical diagnosis of compartment syndrome was based on the presence of increasing pain with passive stretch of the fingers and the presence of massive swelling/tenderness on palpation. Similar to the findings of del Piñal et al (2002), we also found that hard swelling was the most important clinical sign. We also normally perform compartment pressure measurements, but these were not done in the current study because they were not available in that particular hospital.…”
Section: Methodssupporting
confidence: 90%
“…The main problem in these patients is the concomitant vascular injury in which hand amputation is the end-point of treatment unless revascularization is carried out. Finally, perhaps the most common industrial crush injury to the hand is the 'simple closed crush', which is associated with acute hand compartment syndrome (Del Piñal et al, 2002). Here, the impact force is relatively lower than the exploded hand syndrome and the force is not localized across the palm as seen in the balloon hand syndrome.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Дослідження виконано відповідно до принципів Гельсінської декларації. Синдром субфасціальної гіпертензії виникає внаслідок підвищення тиску всередині фаціальних футлярів, який призводить до феномену вазоконстрикції, критичного зменшення перфузії в м'язових і нервових внутрішньофасціальних структурах, для якого характерна типова клінічна тріада -набряк ураженого сегмента, біль і глибоке порушення чутливості [3,4].…”
unclassified
“…Crush injuries of the hand are a common injury. In the typical case, one can expect metacarpal fractures, ragged skin flaps and an unusually high incidence of compartment syndromes (Piñal et al, 2002). “Crush to the carpus” is a much rarer, high-energy injury associated with axial wrist dislocations (Garcia-Elias et al, 1985).…”
mentioning
confidence: 99%